2019
DOI: 10.3389/fphys.2019.00467
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Molecular Spectrum of Glucose-6-Phosphate Isomerase Deficiency. Report of 12 New Cases

Abstract: Glucose-6-phosphate isomerase (GPI, EC 5.3.1.9) is a dimeric enzyme that catalyzes the reversible isomerization of glucose-6-phosphate to fructose-6-phosphate, the second reaction step of glycolysis. GPI deficiency, transmitted as an autosomal recessive trait, is considered the second most common erythro-enzymopathy of anaerobic glycolysis, after pyruvate kinase deficiency. Despite this, this defect may sometimes be misdiagnosed and only about 60 cases of GPI deficiency have been reported. GPI deficient patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 42 publications
0
25
0
Order By: Relevance
“…Eight cases from six families had a biochemical diagnosis of enzyme defect; two were confirmed to have pyruvate kinase (PK) deficiency, three from two families glucose-6-phosphate dehydrogenase (G6PD) deficiency and one was found to have one mutation in GPI gene, in compound heterozygosity with the polymorphism c.489A > G (p.Gly163 = rs1801015), possibly associated to splicing alterations (Fermo et al, 2019); in two related cases no mutations in PKLR gene were found in spite of a slightly decreased PK activity detected by enzymatic assay.…”
Section: Enzyme Defectsmentioning
confidence: 99%
“…Eight cases from six families had a biochemical diagnosis of enzyme defect; two were confirmed to have pyruvate kinase (PK) deficiency, three from two families glucose-6-phosphate dehydrogenase (G6PD) deficiency and one was found to have one mutation in GPI gene, in compound heterozygosity with the polymorphism c.489A > G (p.Gly163 = rs1801015), possibly associated to splicing alterations (Fermo et al, 2019); in two related cases no mutations in PKLR gene were found in spite of a slightly decreased PK activity detected by enzymatic assay.…”
Section: Enzyme Defectsmentioning
confidence: 99%
“…Glucose phosphate isomerase (GPI, EC 5.3.1.9) catalyzes the isomerization reaction of a pyranose six-membered ring in glucose-6-phosphate to a furanose five-membered ring in fructose-6-phosphate. An important feature of identifying a GPI defective enzyme is the change in its physico-chemical properties (thermostability, isoelectric point, and electrophoretic motion) and its kinetic properties (Repiso et al, 2006;Warang et al, 2012;Fermo et al, 2019). Abbreviations for metabolites: ADE, adenine, ADO, adenosine, SAdoHcy, S-adenosylhomocysteine, D13PG, 1,3-biphosphoglycerate, D23PG, 2,3diphosphoglycerate, DHAP, dihydroxyacetone phosphate, ERY4P, erythrose 4-phosphate, F6P, fructose-6-phosphate, FDP, fructose diphosphate, G6P, glucose-6-phosphate, GA3P, glyceraldehydes-3-phosphate, GL6P, 6-phosphogluco lactone, GLC, glucose, GO6P 6-phosphogluconate, GSH, reduced glutathione, GSSG, oxidized glutathione, Hcy, homocysteine, H2O2, hydrogen peroxide, HYPX, hypoxanthine, IMP, inosine monophosphate, INO, inosine, LAC, lactate, P2G, 2-phosphoglycerate, P3G, 3-phosphoglycerate, PEP, phosphenolpyruvate, PRPP, 5-phosphoribosyl pyrophosphate, PYR, pyruvate, R1P, ribose-1-phosphate, R5P, ribose-5-phosphate, RL5P, ribulose-5-phosphate, SAM, S-adenosylmethionine, SED7P, sedoheptulose 7phosphate, XYL5P, xylose-5-phosphate, Gly, glycine, Gln, glutamine, Glu, glutamic acid, Cys, cysteine.…”
Section: Discussionmentioning
confidence: 99%
“…Despite glucosephosphate isomerase (GPI) deficiencies being quite rare, they are the third frequent cause of nonspherocytic hemolytic anemia (Zaidi et al, 2017;Grace & Glader, 2018;Burger et al, 2019) associated with the mutation of the GPI gene. This gene contains 18 exons and produces 1.9 kb mRNA, which encodes a 558 amino acids protein (Lin et al, 2015;Zaidi et al, 2017;Fermo et al, 2019). The molecular characterization of known GPI variants indicates that gene defects are predominantly point mutations (Jamwal et al, 2017;Burger et al, 2019;Fermo et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations